Health Worker Absenteeism in Selected Health Facilities in Enugu State: Do Internal and External Supervision Matter? - Obodoechi, Divine Ndubuisi; Onwujekwe, Obinna; McKee, Martin; Angell, Blake; Agwu, Prince; Orjiakor, Charles; Nwokolo, Chukwudi; Odii, Aloysius; Hutchinson, Eleanor; Balabanova, Dina (Frontiers in Public Health, 2021)
Background: Absenteeism is widespread in Nigerian health facilities and is a major barrier to achievement of effective Universal Health Coverage. We have examined the role of internal (by managerial staff within facilities) and external (by managers at a higher level) supervision arrangements on health worker absenteeism. Specifically, we sought to determine whether these forms of supervision have any role to play in reducing health worker absenteeism in health facilities in Enugu State Nigeria. Methods: We conducted interviews with 412 health workers in urban and rural areas of Enugu State, in South-Eastern Nigeria. We used binary logistic regression to estimate the role of different types of supervision on health worker absenteeism in selected health facilities in Enugu State. Results: Internal supervision arrangements significantly reduce health worker absenteeism (odds ratio = 0.516, p=0.03). In contrast, existing external supervision arrangements were associated with a small but significant increase in absenteeism (OR= 1.02, 0.043). Those reporting a better financial situation were more likely to report being absent (OR=1.36, p<0.01) but there was no association with age and marital status of respondents. Our findings also pointed to the potential for alternative forms of supervision, provided in a supportive rather than punitive way, for example by community groups monitoring the activities of health workers but trying to understand what support these workers may need, within or beyond the work environment. Conclusion: The existing system of external supervision of absenteeism in health facilities in Nigeria is not working but alternatives that take a more holistic approach to the lived experiences of health workers might offer an alternative.